Intention to use a mobile phone to receive mental health support and its predicting factors among women attending antenatal care at public health facilities in Ambo town, West Shoa zone, Ethiopia 2022 - Wabi Temesgen Atinafu; Kefyalew Naniye Tilahun; Tesfahun Melese Yilma; Zeleke Abebaw Mekonnen; Agmasie Damtew Walle; Jibril Bashir Adem (BMC, 2023)
Abstract Background Mental health problems are the most common morbidities of women during the prenatal period. In LMICs mobile phones have been identified as a good vehicle for monitoring individuals with a high risk of mental health conditions. However, evidence is scarce and the purpose of this study was to assess the intention to use a mobile phone to receive mental health support and its predicting factors among women attending antenatal care at public health facilities in Ambo town, Ethiopia 2022. Methods and materials An institutional-based cross-sectional study design was conducted from May 20th to June 20th, 2022. A total of 715 prenatal women were included and a systematic random sampling technique was employed. An interviewer-administered structured questionnaire was used. Collected data was exported to SPSS version 25 for the descriptive part, and AMOS 26 structural equation modeling was also used to describe and assess the degree and significance of relationships between variables. Results A total of 699 (97.8% response rate) responded to complete all the questionnaires. About 530 (77.3%) 95% CI (74%-80.3%) of women intended to use a mobile phone to receive mental health support. The perceived usefulness has a positive effect on attitude (β = 0.391, p < 0.001) and intention to use (β = 0.253, p < 0.001). The perceived ease of use influences perceived usefulness (β = 0.253, p < 0.001) and attitude β = 0.579, p < 0.001). The intention to use is positively affected by attitude (β = 0.662, p < 0.001).Trust has a positive effect on perceived usefulness (β = 0.580, p < 0.001) and intention to use (β = 0.113, p = 0.005). Subjective norm has a direct positive effect on perceived usefulness (β = 0.248, p < 0.001). Attitude serves as a partial mediator between perceived usefulness and intention to use and a complete mediating role between perceived ease of use and intention to use. Conclusion The level of intention to use a mobile phone among prenatal women is relatively high and attitude, perceived usefulness, and trust had direct positive effects on intention to use a mobile phone. Therefore, hospitals and healthcare providers should take proactive measures to implement the strategies and policies for providing mobile phone-based mental health support to prenatal women in remote areas.